Formation on quartz substrate and study of properties of nanostructured layers from polyvinylen obtained by dehydrochlorination of polyvinyl chloride with modifying additive — iron nitrate - O. V. Krivozubov; Yu. G. Kryazhev; I. V. Anikeeva; N. A. Davletkildeev; D. V. Sokolov; O. N. Semenova (Омский научный вестник)
The work is devoted to solving the urgent task of developing simple ways of applying nanostructured layers of polymers to different substrates with a pairing system with properties of organic semiconductors. To obtain such polymers used dehydrochlorination of polyvinyl chloride under the influence of anilin in the solution dimethylsulfoxide. Iron nitrate is used as a metal-containing modifying supplement. The nanostructured layers of polyvinylen (polymer with the system of conjugated double bonds) are obtained by forming on the plates of monocrystalline quartz by the Langmur-Blodgett. The ASM method shows that in the absence of metal-containing additives, layers of polyvinylens are formed thick ~100 nm. Metal addition leads to significant changes in the morphology of the layers. There is a formation of conglomerates of rounded particles measuring ~30…50 nm. The iron content in these layers is 0,04 % atomic. The study of ultraviolet spectrums shows that iron dopation causes a multiple increase in optical density in the entire range of wavelengths studied. The resulting data can be used to create an elemental base of molecular electronics.